Flavor-dependent U(1) extension inspired by lepton, baryon and color numbers - Duong Van Loi; Phung Van Dong (European Physical Journal C: Particles and Fields, 2023)
Abstract There is no reason why the gauge symmetry extension is family universal as in the standard model and the most well-motivated models, e.g. left-right symmetry and grand unification. Hence, we propose a simplest extension of the standard model – a flavor-dependent U(1) gauge symmetry – and find the new physics insight. For this aim, the U(1) charge, called X, is expressed as $$X=x B+y L$$ X = x B + y L in which x and y are free parameters as functions of flavor index, e.g. for a flavor i they take $$x_i$$ x i and $$y_i$$ y i respectively, where B and L denote normal baryon and lepton numbers. Imposing a relation involved by the color number 3, i.e. $$-x_{1,2,… ,n}=x_{n+1,n+2,… ,n+m}=3y_{1,2,… ,n+m}\equiv 3z$$ - x 1 , 2 , … , n = x n + 1 , n + 2 , … , n + m = 3 y 1 , 2 , … , n + m ≡ 3 z , for arbitrarily nonzero z, we achieve a novel U(1) theory with implied X-charge. This theory not only explains the origin of the number of observed fermion families but also offers a possible solution for both neutrino mass and dark matter, which differs from $$B-L$$ B - L extension. Two typical models based on this idea are examined, yielding interesting results for flavor-changing neutral currents and particle colliders, besides those of neutrino mass and dark matter.